2011
DOI: 10.1021/la201972f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Free and Forced BSA Adsorption on a Hydrophobic Graphite Surface

Abstract: The adsorption of bovine serum albumin (BSA) onto a hydrophobic graphite surface is studied using molecular-dynamics simulation. In addition to the free, that is, unsteered, adsorption, we also investigate forced adsorption, in which the action of an AFM tip pushing the protein with constant force to the surface is modeled. Using an implicit inviscid water model, the adsorption dynamics and energetics are monitored for two different initial protein orientations toward the surface. In all cases, we find that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 26 publications
9
88
0
Order By: Relevance
“…Circular dichroism (CD) spectroscopic study by Sivaraman et al demonstrated that adsorption of albumin on hydrophobic CH 3 -SAM induced greater conformational change than on hydrophilic surfaces (OH-, COOH-, NH 2 -SAMs) [34]. Conformational change of adsorbed proteins on hydrophobic surfaces is also shown by molecular simulation [35] and Fourier transform infrared spectroscopy [36]. While strongly (or irreversibly) adsorbing albumin to CH 3 -SAM would inhibit displacement with other proteins in liquid phase, weakly (or reversibly) adsorbing albumin to hydrophilic SAMs would allow for the displacement [32,37].…”
Section: Discussionmentioning
confidence: 98%
“…Circular dichroism (CD) spectroscopic study by Sivaraman et al demonstrated that adsorption of albumin on hydrophobic CH 3 -SAM induced greater conformational change than on hydrophilic surfaces (OH-, COOH-, NH 2 -SAMs) [34]. Conformational change of adsorbed proteins on hydrophobic surfaces is also shown by molecular simulation [35] and Fourier transform infrared spectroscopy [36]. While strongly (or irreversibly) adsorbing albumin to CH 3 -SAM would inhibit displacement with other proteins in liquid phase, weakly (or reversibly) adsorbing albumin to hydrophilic SAMs would allow for the displacement [32,37].…”
Section: Discussionmentioning
confidence: 98%
“…These disturbances may lead to uncertainties in experimental measurements. Particularly, SMD simulations conducted to investigate the effect of the tip of an AFM showed that pushing a molecule towards a surface with an AFM tip will bias the results by increasing adhesion, as the force exerted on the molecule leads it to spread more on the surface (Horinek et al 2008;Mücksch & Urbassek, 2011). With SMD simulations, the adsorption mechanisms of peptides and proteins on different types of surfaces have been investigated (Alvarez-Paggi et al 2010;Dong et al 2007;Emami et al 2014b;Friedrichs et al 2013;Hamdi et al 2008;Shen et al 2008;Utesch et al 2011;Yang & Zhao, 2007) and compared with experimental measurements (Schneider & Colombi Ciacchi, 2010.…”
Section: Non-equilibrium Methodsmentioning
confidence: 99%
“…To alter the hydrophobicity, surface modifications with surface defects and polar groups have been suggested, but these affect the stability of the materials as well as their mechanical and electrical properties (Scida et al 2011). Computational studies of protein-carbon surface interactions have mostly focused on graphene/graphite (Mereghetti & Wade, 2011;Mücksch & Urbassek, 2011;Raffaini & Ganazzoli, 2010;Kang et al 2013;Sun et al 2014b;Yu et al 2012b), CNT (Balamurugan et al 2010;Chen et al 2009b;Tallury & Pasquinelli, 2010;Wang et al 2003) and fullerenes (Durdagi et al 2008;Kraszewski et al 2010;Noon et al 2002).…”
Section: Carbon Allotropesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold in particular can be modeled in common simulation codes such as GROMACS and NAMD using either the GolP atomistic force field [67] or the METAL/INTERFACE force field [68]. Additional materials of interest for bioelectrochemistry can be modeled such as silica [69], but also graphite [70] or carbon nanotubes [71]. These latter materials cannot be considered as planar surfaces, however.…”
Section: Conductive Electrode Surfacesmentioning
confidence: 99%